Cia. Cervejaria Brahama, Passo Fundo, Rio Grande do Sul (1947-1997): paternalismo industrial e nostalgia da chaminé - Palmeiras, Jênifer de Brum (2024)
This thesis has the general objective of analyzing the installation, operation and closing of Cia. Cervejaria Brahma in Passo Fundo, in Rio Grande do Sul, between the years 1947-1997, relating it to strategic decisions guided by changes in economic policy in the regional, national and international context and with the development of the city. The thesis seeks to understand how the process of globalization influenced the company's trajectory, directly impacting the structuring of the Passo Fundo branch and having an impact on the lives of workers, their families and the development of the municipality. In conceptual terms, research is anchored in the idea of ​​industrial paternalism, understood as a set of mechanisms designed to ensure labor productivity, involving attraction and retention of the workforce, followed by discipline in relation to spaces, functions and behaviors, aiming to create a new way of being for the worker and exercise control both in the sphere of production and in the lives of workers. Of Likewise, the nostalgia for the chimney constitutes an important representation in structuring the narrative by invoking loss, rescuing the past and bringing to memory the meaning, for himself and for the community, of working in the industry he was in inserted. The objective is to scrutinize and problematize the components of this experience, inserting it within the scope of Business History, from the perspective of a field interdisciplinary, which articulates the interaction between socioeconomic and political-cultural factors as explanatory vectors for the profile of companies and which requires resorting to diverse sources. As sources of research, the work then resorts to memory of the company's former workers, gathered through testimonies, which provide evidence of lived experiences, compared with primary documentation of historical files and Ambev's collection, press sources and statistical data.